DNA Damage-Induced Inflammatory Microenvironment and Adult Stem Cell Response - Cinat, Davide; Coppes, Robert P.; Barazzuol, Lara (Frontiers in Cell and Developmental Biology, 2021)
Adult stem cells ensure tissue homeostasis and regeneration after injury. Due to their longevity and functional requirements, throughout their life stem cells are subject to a significant amount of DNA damage. Genotoxic stress has recently been shown to trigger a cascade of cell- and non-cell autonomous inflammatory signaling pathways, leading to the release of pro-inflammatory factors and an increase in the amount of infiltrating immune cells. In this review, we discuss recent evidence of how DNA damage by affecting the microenvironment of stem cells present in adult tissues and neoplasms can affect their maintenance and long-term function. We first focus on the importance of self-DNA sensing in immunity activation, inflammation and secretion of pro-inflammatory factors mediated by activation of the cGAS-STING pathway, the ZBP1 pathogen sensor, the AIM2 and NLRP3 inflammasomes. Alongside cytosolic DNA, the emerging roles of cytosolic double-stranded RNA and mitochondrial DNA are discussed. The DNA damage response can also initiate mechanisms to limit division of damaged stem/progenitor cells by inducing a permanent state of cell cycle arrest, known as senescence. Persistent DNA damage triggers senescent cells to secrete senescence-associated secretory phenotype (SASP) factors, which can act as strong immune modulators. Altogether these DNA damage-mediated immunomodulatory responses have been shown to affect the homeostasis of tissue-specific stem cells leading to degenerative conditions. Conversely, the release of specific cytokines can also positively impact tissue-specific stem cell plasticity and regeneration in addition to enhancing the activity of cancer stem cells thereby driving tumor progression. Further mechanistic understanding of the DNA damage-induced immunomodulatory response on the stem cell microenvironment might shed light on age-related diseases and cancer, and potentially inform novel treatment strategies.